2006
DOI: 10.1038/sj.bjc.6602933
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of primary cultures of ovarian epithelial cells identifies novel molecular classifiers of ovarian cancer

Abstract: In order to elucidate the biological variance between normal ovarian surface epithelial (NOSE) and epithelial ovarian cancer (EOC) cells, and to build a molecular classifier to discover new markers distinguishing these cells, we analysed gene expression patterns of 65 primary cultures of these tissues by oligonucleotide microarray. Unsupervised clustering highlights three subgroups of tumours: low malignant potential tumours, invasive solid tumours and tumour cells derived from ascites. We selected 18 genes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 36 publications
1
41
0
1
Order By: Relevance
“…We and others have recently shown BMP signaling to be active in and regulate ovarian cancer cells as well. It has previously been shown that BMP ligands and signaling is increased in ovarian cancer cells in comparison to normal ovarian cells [46; 47]. Similar to previous studies, here we show that BMP ligands and receptors are overexpressed in more than 50% of ovarian cancer tumors and ovarian cancer cell lines (Figure 1, Supplementary Figure 1) and is endogenously active in ovarian cancer cell lines (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
“…We and others have recently shown BMP signaling to be active in and regulate ovarian cancer cells as well. It has previously been shown that BMP ligands and signaling is increased in ovarian cancer cells in comparison to normal ovarian cells [46; 47]. Similar to previous studies, here we show that BMP ligands and receptors are overexpressed in more than 50% of ovarian cancer tumors and ovarian cancer cell lines (Figure 1, Supplementary Figure 1) and is endogenously active in ovarian cancer cell lines (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
“…Supporting a role for BMP2 pathway activation in ovarian cancer, compared with normal ovarian surface epithelium, BMP2 is upregulated in ovarian cancer cells (25) whereas the BMP antagonist Chordin is down-regulated (26). Importantly, increased BMP2 expression in ovarian tumors is correlated with poor patient prognosis (27).…”
Section: Cd1333mentioning
confidence: 94%
“…BMP4 has also been reported to drive tumorigenesis of ovarian cancer cells via the regulation of the proto-oncogene ID3 (40). BMP2 has been reported to be specifically upregulated in ovarian cancer cells as compared with normal ovarian surface epithelium (41). BMP2 also appears to have prognostic significance in ovarian cancer patients; BMP2 expression in tumor tissues from ovarian cancer patients has been shown to be inversely correlated with patient survival (34).…”
Section: Discussionmentioning
confidence: 99%